Innowacyjność fundamentalnym warunkiem przedsiębiorczości powszechnie opartej na wiedzy. Porównania międzynarodowe - Bal-Woźniak, Teresa (Wydawnictwo Uniwersytetu Rzeszowskiego, 2007)
W artykule dowodzi się, że upowszechnianie współcześnie przedsiębiorczości powszechnie opartej na wiedzy, tworzy szansę na przekształcanie środowiska i polepszanie jakości życia w różnych sferach bytu ludzkiego. Za podstawę wnioskowania o przedsiębiorczości jednostek, zespołów, organizacji i społeczności, krajów i regionów Unii Europejskiej, przyjęto wyniki stosowanych od 2001 r. miar innowacyjności w ramach "European Innovation Scoreboard i Key Figures of Science, Technology and Innovation".

The article provides evidence that current promotion of entrepreneurship, which is generally based on knowledge, creates an opportunity to rebuild the environment and improve the quality of life in various spheres of human existence. The process of drawing conclusions about the entrepreneurship of entities, teams, organizations and societies, countries and regions was based on the levels of innovativeness indicators, which are being applied in the frame of "European Innovation Scoreboard and Key Figures of Science, Technology and Innovation" since 2001.
Innovativeness as Fundamental Condition for Entrepreneurship Commonly Based On Knowledge. International Comparison